Immature platelet fraction predicts coagulopathy-related platelet consumption and mortality in patients with sepsis. Issue 144 (August 2016) - Muronoi, Tomohiro; Koyama, Kansuke; Nunomiya, Shin; Lefor, Alan Kawarai; Wada, Masahiko; Koinuma, Toshitaka; Shima, Jun; Suzukawa, Masayuki
Abstract: Introduction: The diagnostic and prognostic value of immature platelet fraction (IPF) in sepsis has not been determined. This study aimed to assess whether IPF is an early predictor of platelet decline due to coagulopathy and is associated with mortality in patients with sepsis. Materials and methods: In total, 149 patients with a platelet count of ≥ 80 × 10 3 /μL on intensive care unit admission (101 with sepsis, 48 controls without sepsis) were prospectively evaluated. We measured IPF on admission and observed for development of subsequent platelet count decline (defined as a > 30% decrease or < 80 × 10 3 /μL) in 5 days, and mortality at 28 days. The absolute immature platelet count (AIPC) was calculated to evaluate thrombopoiesis. Results: Forty-seven patients with sepsis subsequently developed a decrease in platelet count. The IPF was highest in patients whose platelet count decreased, followed by patients without a decrease in platelet count and controls (median, 4.3% [3.1%–8.1%] vs. 3.7% [2.6%–4.6%] vs. 2.1% [1.6%–3.5%], respectively; P < 0.0001). The AIPC was similar in patients with and without a decrease in platelet count (7.6 [4.2–10.0] vs. 5.9 [4.2–8.7] × 10 3 /μL, respectively; P = 0.32). Coagulation derangement was more severe in patients who did than did not subsequently develop a decreased platelet count. Cox regression and receiver operator characteristic curve analysis revealed that IPF was a strong independent predictor of mortality, with accuracy similar to a standard prognostic scoring system. Conclusions: The admission IPF in septic patients predicts a subsequent decrease in platelet count, indicating platelet consumption with ongoing coagulopathy and risk of poor prognosis. Highlights: Immature platelet fraction is increased in the early phase of sepsis due to platelet consumption. Increased immature platelet fraction predicts decrease in platelet count in septic coagulopathy. Immature platelet fraction indicates severe coagulopathy and poor prognosis in septic patients.